Implementation of HOTS-Oriented Problem Based Learning on Science Literacy Ability - Supriyadi, Supriyadi; Tias, Ika Wulandari Utamining; Astuti, Nelly; Sukamto, Ismu; Destini, Frida; Khairani, Fadhilah; Izzatika, Amrina (Jurnal Pendidikan Progresif, 2022)
Implementation of High Order Thinking Skills (HOTS) Based on Problem Based Learning on Science Literacy Ability. Objectives: Knowing and analyzing scientific literacy skills by applying the HOTS-oriented Problem Based Learning (PBL) model. Methods: The type of research in this research is experimental research. The object of research is the implementation of HOTS based on Problem Based Learning (X) on literacy skills (Y). The research subjects were fourth grade students of SD Negeri 5 Metro Pusat. The research design used is a pre-experimental design and uses one form of design, namely the one group pretest-posttest design. This design uses one group, as an illustration, the experimental group. The experimental group is the class that gets treatment in the form to the application of HOTS based on Problem-Based Learning. The HOTS indicators used in this study are identify scientific issues (problems); explain scientific phenomena; using scientific evidence Findings: Based on the results of the data analysis, the pretest score for the scientific literacy ability of students achieved by the experimental class was 9.25 and the posttest score was 11.90. Conclusion: The results of the research that have been carried out show that the application of high order thinking skills (HOTS) based on problem based learning (PBL) to improve scientific literacy skills has the impact of increasing n-gain by 0.21 in the low category. In the analysis of the average n-gain score on the highest scientific literacy ability indicator, namely the use of scientific evidence. Keywords: high order thinking skills (hots), problem based learning, science literacy.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202236